Comparison of GPS Collars and Solar-Powered GPS Ear Tags for Animal Movement Studies - Dylan G. Stewart; Egleu D.M. Mendes; Kiju Lee; Marcus E. Blum; Luis O. Tedeschi; Stephen L. Webb (Smart Agricultural Technology)
Animal-borne tracking systems have provided unique insights into when, where, why, and how animals move and interact with the environment. GPS neck collars have been the standard for animal tracking studies, especially for mid to large-size mammals. However, new technological developments have helped to miniaturize tracking devices (e.g., GPS ear tags), including battery size and longevity (e.g., using solar panels). We initiated this study to quantify the difference in horizontal error and data loss between solar-powered GPS mOOvement version 1 ear tags and GPS Vectronic Aerospace collars during stationary testing and while deployed on beef cows (Bos taurus). Mean horizontal error was 41 m (± 1.8 SE) and 2 m (± 0.1 SE) for GPS ear tags and collars during stationary testing, respectively; during animal testing, the distance between paired ear tag and collar locations was 59.2 m (± 3.3 SE). Fix acquisition was 99.3% ± 0.3 SE for ear tags and 99.8% ± 0.2 SE for collars during stationary testing. During animal deployment, fix acquisition changed to 30.7% (± 9.1 SE) and 100% for ear tags and collars, respectively. Lower acquisition rates, driven by loss of battery life, and greater horizontal error of GPS ear tags, while on animals, may introduce bias into estimates of movement and space use; GPS collars appear to be less sensitive to these forms of bias. However, mOOvement GPS ear tag systems are more economical than commercially manufactured GPS collars. Therefore, budgetary constraints, data resolution, and study objectives will dictate which technology to use.